A Study of Code Mixing on “Agak Laen” Podcast - Permata, Meiga; Yani, Juli; Goziyah, Goziyah (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The language used for interaction can be characterized by symbols that are arbitrary in nature. Indonesia, with its vast linguistic diversity, often experiences phenomena like code mixing in daily conversations, which reflects the dynamic interplay between different languages. One setting where this can be observed is in podcasts, which are increasingly popular in Indonesia. In the podcast "Agak Laen," uploaded to YouTube on July 17, 2023, titled Batak Satu Ini kan Yang Kalian Tunggu-tunggu, Raditya Dika, the conversation showcases a blend of languages, a common occurrence in Indonesia's multilingual environment. This study employs a qualitative research method with descriptive analysis to explore the use of multiple languages in the podcast. The analysis reveals that three languages are predominantly used: Indonesian, English, and the Medan regional language. Through these languages, various instances of code mixing emerge, illustrating how speakers fluidly transition between languages during casual conversations. The data collection was conducted using the Listen and Note Technique, which enabled the identification of several notable instances of code mixing throughout the podcast video. This research highlights the natural blending of languages in media content, emphasizing the linguistic hybridity prevalent in modern Indonesian communication, especially in the digital realm. Podcasts like Agak Laen serve as a rich source for analyzing how speakers navigate multilingualism, reflecting broader social and cultural patterns in language use in contemporary Indonesia.